The Role of Gamification and Artificial Intelligence Stimuli in Driving Customer Engagement: A Study on Saudi Telecom Users’ Ability Readiness - Sabaa , Sania; Sumarmi , Saptaningsih; Al-Hariry, Basma; Soliman, Ahmed; Elwakeel, Neama (American Journal of Business Science Philosophy, 2025)
This study examines the impact of gamification in marketing and artificial intelligence (AI) stimuli on customer engagement, with customer ability readiness as a moderating factor in the Saudi telecommunications sector. Using the Stimulus-Organism-Response (SOR) model, this research investigates how AI-driven personalization and gamification strategies influence customer interactions, motivation, and loyalty. A quantitative research approach was employed, utilizing Structural Equation Modeling (SEM) to analyze survey responses from 400 Saudi telecom users. The results confirm that gamification and AI stimuli positively influence customer engagement, with customer ability readiness significantly moderating these relationships. Consumers with higher technological proficiency are more likely to benefit from AI-driven and gamified experiences, while those with lower readiness may struggle to engage effectively. These findings highlight the importance of designing adaptive and inclusive marketing strategies tailored to different levels of digital proficiency. This study contributes to the theoretical literature by expanding the SOR model to include customer ability readiness as a moderating factor. It also provides practical insights for marketers in the Saudi telecom industry, emphasizing the need for personalized, user-friendly AI and gamification strategies. The findings align with Saudi Vision 2030’s goals of digital transformation and customer-centric innovation, offering valuable implications for businesses seeking to enhance customer engagement.
Keywords: gamification; artificial intelligence; engagement; digital marketing; readiness